2015
DOI: 10.1128/iai.01086-15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pla Protease Substrate α2-Antiplasmin on the Progression of Primary Pneumonic Plague

Abstract: Many pathogens usurp the host hemostatic system during infection to promote pathogenesis. Yersinia pestis, the causative agent of plague, expresses the plasminogen activator protease Pla, which has been shown in vitro to target and cleave multiple proteins within the fibrinolytic pathway, including the plasmin inhibitor ␣2-antiplasmin (A2AP). It is not known, however, if Pla inactivates A2AP in vivo; the role of A2AP during respiratory Y. pestis infection is not known either. Here, we show that Y. pestis does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Measurement of plasmin activity. Plasmin activity was determined as described previously (10). BALF (100 l) was incubated in the presence of 50 M D-AFK-ANSNH-iC4H9-2Hbr fluorogenic substrate (SN5; Hematologic Technologies), and fluorescence was recorded over time at 460 nm in 96-well plates with a Molecular Devices SpectraMax M5 fluorescence microplate reader.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of plasmin activity. Plasmin activity was determined as described previously (10). BALF (100 l) was incubated in the presence of 50 M D-AFK-ANSNH-iC4H9-2Hbr fluorogenic substrate (SN5; Hematologic Technologies), and fluorescence was recorded over time at 460 nm in 96-well plates with a Molecular Devices SpectraMax M5 fluorescence microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…plague (7,8), manipulates programmed cell death pathways and deregulates the host fibrinolysis pathways (9). Not only does Pla activate host plasminogen into plasmin, but it also inactivates inhibitors of plasmin activation, ␣ 2 -antiplasmin and plasminogen activation inhibitor 1 (PAI-1) (10,11). In the absence of catalytic activity of Pla, Y. pestis fails to proliferate in the lungs and poorly disseminates into the bloodstream (7).…”
mentioning
confidence: 99%
“…Based upon the data presented here and collected by our group and others previously, we propose classifying substrates of Pla into three categories: group I substrates that are cleaved both in vitro and in vivo and contribute to bacterial virulence and the host response (these substrates would be represented by the apoptotic molecule FasL [43]); group II substrates such as Prdx6 that are cleaved in vitro and in vivo but do not play a detectable role in bacterial virulence or the host response; and finally, group III substrates that are cleaved in vitro but not in vivo and thus have a limited role during disease progression; A2AP would be a representative example of this class of substrate (50). Therefore, while the identification of new host substrates of Pla in vitro can provide new insights into the mechanisms by which Y. pestis causes disease in mammals, it is important to consider that any individual host substrate may not necessarily play a role in vivo, at least at our current level of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…As Pla is required for the full virulence of Y. pestis during pneumonic plague (34,35), we set out to determine if (i) the total levels of Prdx6 are altered in the lungs of mice during respiratory infection with Y. pestis and (ii) if Pla cleaves Prdx6 in vivo. As the ⌬pla mutant of Y. pestis is attenuated during respiratory infections (35), to compare the effects of Pla on Prdx6 levels when bacterial loads are normalized between the wild-type and ⌬pla strains, we can increase the inoculum of the ⌬pla mutant ("input CFU") so that the CFU in the lungs at 48 h ("output CFU") is equivalent between the wild-type and mutant strains, as we have done previously (43,50). To do so, we infected C57BL/6 mice via the i.n.…”
Section: Identification Of Pla Substrates Within Mouse Balfmentioning
confidence: 99%
“…pestis to cause primary pneumonic plague [17]. Also, it was shown that Pla can directly inactivate major plasmin inhibitor α 2 -antiplasmin [18, 19] and mediate adhesion to eukaryotic cells (extracellular matrices and basement membranes) which invasive bacteria must penetrate in order to reach the circulation [20, 21]. In addition to its role in adhesion, invasion and tissue damage, Pla has been reported to cleave complement component C3 [11, 22], to possess weak coagulase activity [15], and to mediate the proteolysis of Yersinia virulence factors Yops [23].…”
Section: Introductionmentioning
confidence: 99%